“AN ANALYSIS OF BRAND LOYALTY AND CONSUMERS OF ORGANIC FRUIT, IN CONTEXT OF THE POSSIBLE INTRODUCTION OF A “WATER-WISE” TABLE GRAPE VARIETY - CASE STUDY AT WOOLWORTHS IN CAPE TOWN” - Borel-Saladin, Brigitte (The IIE, 2018)
The introduction of a sustainable water-wise table grape variety is a possibility that is believed to gain attention amongst organic fruit consumers, if marketed and branded properly. Due to the increasing demand to be more water-wise in this current time of water-crisis in the Cape Region of South Africa, societal expectations are pressing consumers to consider products that are more environmentally friendly. Organic fruit consumers generally strive to associate themselves with a brand that is committed to improving sustainable environmental outcomes, and are health conscious. The research findings indicate that, due to a lack of current information on new water-wise table grape varieties, organic consumers are still on the fence about such a product. It was however found that more and more organic consumers are less strict organic purchasers, which is positive news for the potential new brand. By establishing an innovative brand and communicating accurate information related to quality, taste, health and environmental sustainability the research report concluded that there indeed is a place for this new brand in the agricultural market.
Keywords: Brand; Brand loyalty; Sustainability; Brand - water